Measurement of Alpha Emitters Concentration in Imported Cigarettes - Nasser Allah, Zainab K; Musa, Wasen A; Al-Rawi, Ammar A S (Al-Nahrain Journal of Science, 2011)
The aim of this study was to measured the alpha emitters concentration of (15) different kinds of imported cigarettes. The nuclear reaction used U-235(n, f) obtained by the bombardment of U-235 with thermal neutrons from (Am-Be) neutron source with thermal flux of (5×10^3 n. cm^-2. s^-1). The Results obtained showed the values of the Uranium concentration, and varies from (0.041 ppm) in five stares kind to (2.374 ppm) in Macbeth (chocolate) 100΄s kind. All the result obtained are within the limit levels as given by UNSCAR data.